One Health: From Concept to Practice - Mackenzie, John; McKinnon, M.; Jeggo, M. (Springer, 2014)
One Health (OH) is an approach, focusing on emergent infectious diseases, which looks at health in the context of human, animal and environment relationships. Governments worldwide through the International Ministerial Conferences on Avian and Pandemic Influenza (IMCAPI) meetings have made a commitment to OH. There is unanimous agreement from the international organizations to the community level that this is a necessary approach in an increasingly populous world. It is a world, however, in which professions have moved to specialization and expertise within their own realm rather than in collaboration and cross discipline. This chapter reports on the operationalization of OH to date and consideration of the forward path in examination of the key areas of: leadership, relationships, infrastructure, skills and capacity, communication and technology, and resources.